Lithuanian Economy and Ecology in the Period of the Centrally Planned Economy - Čepinskis, Jonas (Ekonomika, 1996)
All economic systems work in their awn ecological environment, affect the environment and are affected as well. The system of centrally planned economy which was practiced in Lithuania for fifty years had a great impact on the ecological situation of the country. The irresponsible development of chemical industry, agriculture, building industry, and other branches of industry, resulted in a fast deterioration on the environmental situation.The article views the development of the Lithuania centrally planned economy, its impact on the environment system, and the ways of using environmental resources. In order to minimize environmental problems caused by industry, it is necessary to know the history of industrial development and its reasons. The phrase “The future began yesterday” is essential in trying to realize, crystallize, and estimate the relations and contradictions between the economy and ecology that lead to environmental crisis.